A review of the potential socioeconomic impacts of bamboo plantation on local community - Samdin, Zaiton; Abdullah Zawawi, Nurul Izzati; Saadun, Norzanalia; Kamaruddin, Norfaryanti (Universiti Putra Malaysia Press, 2024)
Bamboo is a versatile and essential resource that thrives in tropical climates, providing shelter, tools, and even a staple vegetable in Asia, Africa, and South America. This paper reviews the potential socioeconomic impact of bamboo plantations on local communities, emphasizing the relevance of bamboo cultivation across different cultural and environmental contexts. It delves into the multifaceted potential of bamboo, moving beyond its historical significance, and describes the plant's adaptability, showcasing its transformative application in construction, medicine, energy, and beyond. The goal is to synthesize existing knowledge and insights on the subject, providing a valuable resource for policymakers, researchers, and industry stakeholders. By consolidating existing knowledge globally, it offers an understanding of the potential benefits, challenges, and strategies associated with bamboo plantations. It is hoped that this review can serve as a foundational resource for those seeking to promote the growth of the bamboo industry while enhancing the well-being of local communities. It is intended for publication in a scholarly journal to disseminate this knowledge globally, fostering informed decision-making and sustainable practices in agroforestry and bamboo cultivation across diverse regions.